Takayasu arteritis associated with tuberculosis: a case report - Anusha, Are; Shree, Malvey Anusha; Chandrika, G. Naga; Mandava, Kiranmai; Anusha, Manda (International Journal of Basic & Clinical Pharmacology, 2023)
Takayasu arteritis, also called pulseless disease, is the chronic inflammation of the vessels, mainly the aorta and large vessels. It mainly affects females more than males with the ratio of 2.15:1 and in the second and third decade of life. Mechanism may be transmural fibrous thickening of the arterial walls. Takayasu’s is characterized by granulomatous inflammation of the vessel wall, leading to occlusion of the vessel wall. It is represented with claudication, fever, arthralgia. Clinical features are chest pain, vascular bruits, Hypertension. Investigation is based on angiography and CT scan. Medical treatment prednisolone is the first line agent 1mg/kg/day maximum dose is 60mg/day with gradual tapering as per European league against rheumatism guidelines, methotrexate and azathioprine are for inducing remission of arterial lesions, tumour necrosis factor-a antagonists, anti-IL-6 receptor monoclonal antibody like tocilizumab. Surgical treatment is angioplasty and stenting renal artery stenosis but less invasive and safest method is percutaneous transluminal angioplasty (PTA). Takayasu arteritis might be associated with Tuberculosis, yet, the relationship and mechanism are not clearly understood. Here we report a case of Takayasu arteritis associated with tuberculosis.